2017
DOI: 10.1038/nmat4907
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer dynamics and nonlocal dielectric permittivity tuned with metamaterial structures as solvent analogues

Abstract: Charge transfer (CT) is a fundamental and ubiquitous mechanism in biology, physics and chemistry. Here, we evidence that CT dynamics can be altered by multi-layered hyperbolic metamaterial (HMM) substrates. Taking triphenylene:perylene diimide dyad supramolecular self-assemblies as a model system, we reveal longer-lived CT states in the presence of HMM structures, with both charge separation and recombination characteristic times increased by factors of 2.4 and 1.7-that is, relative variations of 140 and 73%, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 62 publications
3
61
0
Order By: Relevance
“…Lastly, the overall efficiency of charge transfer of this complex interface is not as high as that observed in other nanomaterials ( 7 , 15 ). Yet, it could be enhanced by optical engineering, for example, using mesoscopic framework ( 66 ) to prepare interfaces with a larger surface area or using hyperbolic metamaterials ( 67 ) to enhance charge transfer rate.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the overall efficiency of charge transfer of this complex interface is not as high as that observed in other nanomaterials ( 7 , 15 ). Yet, it could be enhanced by optical engineering, for example, using mesoscopic framework ( 66 ) to prepare interfaces with a larger surface area or using hyperbolic metamaterials ( 67 ) to enhance charge transfer rate.…”
Section: Discussionmentioning
confidence: 99%
“…AFM 3D images for PEDOT:PSS films had revealed areas of smaller and larger heights which are represented in the image by light and dark areas respectively. These bright and dark areas are commonly associated with PEDOT and PSS rich regions [25,26]. The low RMS value for the pristine PEDOT:PSS film of 1.124 nm implied its smooth surface (Figure 9).…”
Section: Morphology Characterization Of Pedot:pss-atomic Force Microsmentioning
confidence: 99%
“…Recently, the reduction of both charge separation and charge recombination rates in the triphenylene: perylene diimide dyad {TriPh(donor): PerDi(acceptor)} has been observed in vicinity of metallic surfaces and lamellar metal-dielectric metamaterials 31 . The qualitatively similar effect (reduction of the recombination rate) has been reported in the p3ht:PC 60 BM polymer blend 31 . These two experiments show the generality of our recent finding 17 (reduction of the rate of a chemical reaction in vicinity of metal).…”
Section: Discussionmentioning
confidence: 99%
“…The results of ref. 31 have been explained in terms of the modified Marcus theory. In particular, it has been shown that interaction of molecular dipoles with their mirror images reduces the dipole energy the same way as modification of the local dielectric permittivity does, leading to the reduction of the reaction rates.…”
Section: Discussionmentioning
confidence: 99%